Pemberdayaan Perempuan Korban Kekerasan Seksual - Annisa Pratiwi Rosjayani; Dindin Solahudin; Muh Idham Kurniawan (Tamkin: Jurnal Pengembangan Masyarakat Islam, 2022)
Sexual violence against women is a social problem that cannot be avoided. The policy of UPT PPA as a provider of protection services for women victims of sexual violence and empowerment carried out by UPT PPA Makassar is through training. This paper aims to identify forms of sexual violence against women, describe the implementation of women's empowerment for victims of sexual violence and measure the success rate of women's empowerment programs. This study uses a qualitative method with a descriptive approach, the data used in the form of empirical data and obtained through observations and interviews and accompanied by the results of documentation. The results showed that victims of sexual violence against women there were forms of violence, namely rape and sexual harassment. Therefore, the efforts made by UPT PPA Makassar help victims so that they gradually recover and improve psychologically. Victims of sexual violence after receiving recovery can be empowered with sewing training and show their identity as women and can change economic conditions so that women can empower themselves and be more independent.